2023
DOI: 10.3390/toxics11020127
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to Polypropylene Microplastics via Oral Ingestion Induces Colonic Apoptosis and Intestinal Barrier Damage through Oxidative Stress and Inflammation in Mice

Abstract: Extensive environmental pollution by microplastics has increased the risk of human exposure to plastics. However, the biosafety of polypropylene microplastics (PP-MPs), especially of PP particles < 10 μm, in mammals has not been studied. Thus, here, we explored the mechanism of action and effect of exposure to small and large PP-MPs, via oral ingestion, on the mouse intestinal tract. Male C57BL/6 mice were administered PP suspensions (8 and 70 μm; 0.1, 1.0, and 10 mg/mL) for 28 days. PP-MP treatment resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 128 publications
1
22
0
Order By: Relevance
“…Another study offered preliminary data that oral consumption of PPMPs causes a redox system imbalance as colonic epithelial cells from mice indicated mitochondrial damage after being subjected to PPMPs with sizes of 8 μm and 70 μm and concentrations of 1 and 10 mg mL −1 , and minor abnormalities in mitochondrial structures, including vacuolation, loose ridge arrangement decreased matrix and partial swelling, were observed. 52 Meanwhile, another study consisting of a novel 3D in vitro intestinal model showed that MPs at concentrations of 823.5–1380 μg cm −2 of size 50–500 μm did not show any significant cytotoxicity as well as no changes in barrier integrity. 53 Another study, revealed that MP phagocytosis decreases murine macrophage mitochondrial respiration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study offered preliminary data that oral consumption of PPMPs causes a redox system imbalance as colonic epithelial cells from mice indicated mitochondrial damage after being subjected to PPMPs with sizes of 8 μm and 70 μm and concentrations of 1 and 10 mg mL −1 , and minor abnormalities in mitochondrial structures, including vacuolation, loose ridge arrangement decreased matrix and partial swelling, were observed. 52 Meanwhile, another study consisting of a novel 3D in vitro intestinal model showed that MPs at concentrations of 823.5–1380 μg cm −2 of size 50–500 μm did not show any significant cytotoxicity as well as no changes in barrier integrity. 53 Another study, revealed that MP phagocytosis decreases murine macrophage mitochondrial respiration.…”
Section: Resultsmentioning
confidence: 99%
“…Another study provided fresh insight into the hazardous effects of MPs on mammals by showing that PPMPs (8 and 70 μm) can harm the intestinal barrier and cause colonic apoptosis in mice by oxidative stress and activation of the TLR4/NF-B inflammatory signal pathway. 110 Reactive oxygen species (ROS) and antioxidant enzymes like glutathione- S -transferase (GST), glutathione reductase (GR) and glutathione peroxidase (GPx) were induced in the monogonont rotifer ( Brachiounus koreanus ) in response to microplastics. 111 In our study, NP-PPMPs triggered higher apoptosis than aged-PPMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus present in the intestines has a protective function and prevents the adhesion of microorganisms [ 126 ]. Mice exposed to oral polypropylene showed a decrease in mucus production and the destruction of the intestinal mucosal barrier in response to oxidative damage and altered inflammatory cytokine levels [ 127 ]. It can be assumed that MP-PET initially caused the loss of microvilli, to which the body responded with increased mucus secretion as a defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the intestinal microflora was revealed in mice treated with MPs [ 21 , 22 , 23 , 24 , 25 ]. According to a number of authors, exposure to MPs causes mild or moderate inflammation in the colon, characterized by weak inflammatory infiltration of the mucosa, the activation of pro-inflammatory signaling pathways, and the increased expression of pro-inflammatory cytokines [ 17 , 23 , 24 , 26 , 27 , 28 , 29 , 30 ]. Violations of antioxidant defense and the development of oxidative stress were revealed [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%